Interplay between Mutations and Efflux in Drug Resistant Clinical Isolates of Mycobacterium tuberculosis - Machado, Diana; Coelho, Tatiane S.; Perdigão, João; Pereira, Catarina; Couto, Isabel; Portugal, Isabel; Maschmann, Raquel De Abreu; Ramos, Daniela F.; von Groll, Andrea; Rossetti, Maria L. R.; Silva, Pedro A.; Viveiros, Miguel (Frontiers in Microbiology, 2017)
Numerous studies show efflux as a universal bacterial mechanism contributing to antibiotic resistance and also that the activity of the antibiotics subject to efflux can be enhanced by the combined use of efflux inhibitors. Nevertheless, the contribution of efflux to the overall drug resistance levels of clinical isolates of Mycobacterium tuberculosis is poorly understood and still is ignored by many. Here, we evaluated the contribution of drug efflux plus target-gene mutations to the drug resistance levels in clinical isolates of M. tuberculosis. A panel of 17 M. tuberculosis clinical strains were characterized for drug resistance associated mutations and antibiotic profiles in the presence and absence of efflux inhibitors. The correlation between the effect of the efflux inhibitors and the resistance levels was assessed by quantitative drug susceptibility testing. The bacterial growth/survival vs growth inhibition was analyzed through the comparison between the time of growth in the presence and absence of an inhibitor. For the same mutation conferring antibiotic resistance, different MICs were observed and the different resistance levels found could be reduced by efflux inhibitors. Although susceptibility was not restored, the results demonstrate the existence of a broad-spectrum synergistic interaction between antibiotics and efflux inhibitors. The existence of efflux activity was confirmed by real-time fluorometry. Moreover, the efflux pump genes mmr, mmpL7, Rv1258c, p55, and efpA were shown to be overexpressed in the presence of antibiotics, demonstrating the contribution of these efflux pumps to the overall resistance phenotype of the M. tuberculosis clinical isolates studied, independently of the genotype of the strains. These results showed that the drug resistance levels of multi- and extensively drug resistant M. tuberculosis clinical strains are a combination between drug efflux and the presence of target-gene mutations, a reality that is often disregarded by the tuberculosis specialists in favor of the almost undisputed importance of antibiotic target-gene mutations for the resistance in M. tuberculosis.